Pemanfaatan Media Manipulatif dalam Pembelajaran Matematika untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Kelas VI - Rahmat, Rahmat; Asrori, M.; Hairida, Hairida (AS-SABIQUN, 2023)
This study is a classroom action research that looks at whether manipulating media can improve motivation and learning results. Its goal is to describe how manipulative media are used in math learning. using descriptive methods carried out in four stages with direct observation techniques, questionnaire questionnaires and measurements using observation sheets, questionnaire sheets, and written tests in the form of fill-in-the-blank questions. Based on the analysis of the teacher's ability to design manipulative media, an average cycle of 1 meeting 1=3.33, meeting 2=3.44, cycle 2 meeting 1=3.67, meeting 2=3.89. The power of teachers to help students learn came from average cycle 1 meeting 1 = 3.30, meeting 2 = 3.48, cycle 2 meeting 1 = 3.65, meeting 2 = 3.87. Learning motivation was obtained on average pre-cycle = 71.15 / 56.92%, after cycle 1 = 85.12 / 68.10%, after cycle 2 = 101.94 / 81.60%. Learning outcomes were obtained on average cycle 1 meeting 1=71.52, meeting 2=78.64, cycle 2 meeting 1=85.00, meeting 2=91.52. Based on these facts, we can say that manipulative media can make students more interested in learning and help them learn more.